Proximal composition and functional properties of lyophilizated surimi of Dosidicus gigas “jumbo squid” (Scientia Agropecuaria, 2017)
The purpose of the research was to determinate proximal composition and functional properties of the giant squid freeze-dried surimi (Dosidicus gigas). Surimi elaborated from giant squid and it lyophilized until obtaining surimi powder to evaluate its characteristics and functional properties. The protein content was 58.7% and carbohydrate 30.5%. Protein solubility in water and salt (3%) were 21.1% and 40.6% respectively, these values being higher than surimi powder of commercial species. The gelling capacity was 2.4% and the emulsifying capacity was 79.9% at a concentration of 1.0%. The color on the Hunter scale was L*: 91.5; a*: 0.5; b*: 7.0. Giant squid powder surimi considered as a functional protein powder due to its percentage protein content, and had good technological characteristics and great potential in the food industry.
Keywords: surimi; jumbo squid; Dosidicus gigas; protein functional properties